Evaluasi Asesmen Diagnostik Terhadap Keadilan Penilaian Belajar Di Madrasah Ibtidaiyah - Nabilatul Imamah; Imron Fauzi; M. Ilmil Zawawi (Publikasi Inspirasi Indonesia, 2025)
This study aims to evaluate the implementation of diagnostic assessment in Madrasah Ibtidaiyah from the perspectives of technical quality and fairness principles. Using a mixed-methods approach with an explanatory sequential design, the research was conducted in three Madrasah Ibtidaiyah in Jombang Regency involving 12 classroom and Islamic Education teachers, 180 fourth- and fifth-grade students, and three principals. Quantitative data from diagnostic assessment results were analyzed using descriptive statistics and t-tests, while qualitative data were collected through interviews, observations, and document analysis. The findings show significant differences between classes (t = 3.47; p = 0.001 < 0.05), indicating variation in learning outcomes due to school context and assessment instrument quality. Although most Islamic Education teachers recognize the importance of diagnostic assessment, it is still used administratively, focused on cognitive aspects, and lacks follow-up actions such as enrichment or remedial programs. Triangulation identifies obstacles such as limited teacher competence, varied assessment designs, and insufficient systematic school policies. The study concludes that diagnostic assessment in Madrasah Ibtidaiyah has not fully reflected fairness principles and needs improvement by integrating technical accuracy, learning context, and Islamic educational values.